PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA KARYAWAN: KAJIAN LITERATUR TERSTRUKTUR - Nauli, Mawar; Simangunsong, Ruben; Gok Asi Sinambela, Julivacius; Nauli, Kembang; Sitepu, Jupianus (Penerbit Lafadz Jaya, 2025)
Transformational leadership plays an important role in improving employee performance through four main components: idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. This study examines the effect of transformational leadership on employee motivation, engagement, and performance through a literature review that groups study into three main clusters: leadership components, impact on motivation and commitment, and impact on performance. The results of the study indicate that transformational leaders who are able to inspire and motivate employees will improve individual and team performance. However, the effectiveness of this leadership style is influenced by cultural factors and organizational structure. Therefore, further research with quantitative and qualitative approaches is needed to test the concept of a model that enlightens and enriches understanding of the context of transformational leadership implementation in various sectors and cultures.